The bank liquidity channel of financial (in)stability - Joshua Bosshardt; Ali Kakhbod; Farzad Saidi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We examine the system-wide effects of liquidity regulation on banks' balance sheets. In the general equilibrium model, banks have to hold liquid assets, and choose among illiquid assets varying in the extent to which they are difficult to value before maturity, e.g., structured securities. By improving the liquidity of interbank markets, tighter liquidity requirements induce banks to invest in such complex assets. We evaluate the welfare properties of combining liquidity regulation with other financial-stability policies, and show that it can complement ex-ante policies, such as asset-specific taxes, whereas it can undermine the benefits of ex-post interventions, such as quantative easing.
Keywords: E44; G01; G21; G28; 330; liquidity regulation; securitization; interbank markets; financial stability; quantitative easing